(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Modern conditions determine the mutual exchange of property and the need to form clear conditions for assessing the value of assets. The value of a business is an important assessment indicator that provides an objective assessment and reduces the likelihood of disputes. Any financial transaction, whether it is an investment, the sale of assets or management decisions, operations related to a mortgage or inheritance, requires the conduct of an assessment process. This article examines the features of assessing the value of a business and develops approaches to implementing this process.